2019
DOI: 10.1017/s0014479719000048
|View full text |Cite
|
Sign up to set email alerts
|

Gains in grain yield of released maize (Zea mays L.) cultivars under drought and well-watered conditions

Abstract: Maize (Zea mays L.) grain yield is severely constrained by drought and this study was conducted to assess gains in grain yield and other traits of released maize cultivars. Twenty-three maize cultivars plus a check were evaluated under drought and well-watered conditions at Zaria and Kadawa during 2015/2016 and 2016/2017 dry seasons. The 24 cultivars were evaluated using 6 x 4 lattice design with three replications. Genotypes differed significantly for all measured traits except anthesis-silking interval (ASI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
(17 reference statements)
1
7
1
Order By: Relevance
“…The significant mean squares detected for GY and most measured traits for the 60 extra-early hybrids under both drought and well-watered conditions suggested high genetic variability among the hybrids under both moisture stress and optimal growing conditions. The significant Env × hybrid (period), and period mean squares indicated that the hybrids performed differently under contrasting moisture conditions within different periods and that the environments and the periods were distinct enough to reveal the differences among the genotypes [10,25,39]. These results also suggested large variability in environmental factors particularly soil type (water holding capacity) and rainfall amount [40], as well as temperature ranges during the growing seasons at the experimental site, particularly at Ikenne.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The significant mean squares detected for GY and most measured traits for the 60 extra-early hybrids under both drought and well-watered conditions suggested high genetic variability among the hybrids under both moisture stress and optimal growing conditions. The significant Env × hybrid (period), and period mean squares indicated that the hybrids performed differently under contrasting moisture conditions within different periods and that the environments and the periods were distinct enough to reveal the differences among the genotypes [10,25,39]. These results also suggested large variability in environmental factors particularly soil type (water holding capacity) and rainfall amount [40], as well as temperature ranges during the growing seasons at the experimental site, particularly at Ikenne.…”
Section: Discussionmentioning
confidence: 88%
“…It was believed that assessment of the genetic improvement in terms of grain yield and related agronomic traits from one breeding period to the other during the past two decades could be beneficial in identifying important traits to accelerate genetic gains in the hybrid development program [22,23]. However, the direct relationship between grain yield potential and related traits of the drought-tolerant extra-early hybrids developed during the three breeding periods [24] had not been assessed to understand the rationale behind the huge investments in the breeding program [25]. It is therefore of vital importance to determine the extent of progress made in breeding for extra-early hybrids tolerant to drought in the specified breeding periods.…”
Section: Introductionmentioning
confidence: 99%
“…Information on trait association is important for designing effective breeding programs for maize genetic enhancement [22]. The significant and negative correlations obtained for grain yield and Striga damage and number of emerged Striga plants at 8 and 10 WAP implied that these characters were important for yield improvement under Striga infestation.…”
Section: Performance Assessment Of Grain Yield Stability Of Early Matmentioning
confidence: 99%
“…Several authors [10][11][12][13][14][15] have reported genetic gain studies for comparisons of older and newer cultivars under different environments, and they have significantly contributed to better understanding of the breeding progress of maize cultivars developed during different periods [16,17]. Results of genetic gain studies have revealed significant increases in grain yield between generations of cultivars.…”
Section: Introductionmentioning
confidence: 99%